Case report: Intracranial lesions of cat-scratch disease mimicking an atypical meningioma - Fang, Qiang; Wang, Pengju; Qin, Shanshan; Liu, Shangxin; He, Jingzhen (Frontiers in Neurology, 2023)
Objectives Cat-scratch disease (CSD) is an infectious disease caused by Bartonella henselae. The most typical symptom of patients with CSD is regional lymphadenopathy, while central nervous system lesions related to CSD are rare. Here, we present a case of an aged woman with CSD involving the dura mater with a manifestation similar to that of an atypical meningioma. Methods The patient was followed up by our neurosurgery and radiology teams. Clinical information was recorded, and the pre- and post-operation CT results and magnetic resonance imaging (MRI) changes were collected. The paraffin-embedded tissue was sampled for the polymerase chain reaction (PCR) test. Results In this study, we present the details of a 54 year-old Chinese woman admitted to our hospital with a paroxysmal headache for 2 years that had worsened in the past 3 months. Brain CT and MRI showed a meningioma-like lesion below the occipital plate. En bloc resection of the sinus junction area was performed. A pathological examination showed granulation tissue and fibrosis with acute and chronic inflammation, granuloma, and central stellate microabscess, which was suspected as the cat-scratch disease. The paraffin-embedded tissue was sampled for a polymerase chain reaction (PCR) test to amplify the corresponding pathogen gene sequence, which was Bartonella henselae. Conclusion The case in our study underscores the fact that the incubation period of CSD may be very long. On the contrary, CSD can involve the meninges, resulting in tumor-like lesions.